Seasonality and global public interest in psoriasis: an infodemiology study. Issue 1133 (11th September 2019) - Wu, Qian; Xu, Zhiwei; Dan, Yi-Lin; Zhao, Chan-Na; Mao, Yan-Mei; Liu, Li-Na; Pan, Hai-Feng
Abstract: Objective: Although patients with psoriasis frequently report seasonal changes in their symptoms, the seasonality of psoriasis has rarely been explored. This study aims to investigate the seasonal pattern of and global public interest in psoriasis using Google search data. Methods: Internet search data were collected from Google Trends. Data on the relative search volume (RSV) from January 2004 to December 2018 were retrieved using the term psoriasis. Cosinor analyses were conducted to examine the seasonality of psoriasis using data from two southern hemisphere countries (Australia and New Zealand) and four northern hemisphere countries (USA, Canada, UK and Ireland). Results: Overall, searches for psoriasis steadily decreased between 2004 and 2010, and then rose from 2011 to 2018. On cosinor analyses, RSV of 'psoriasis' displayed a significant seasonal variation worldwide ( p <0.025). Further analyses confirmed the seasonality of psoriasis-related RSV in Australia, New Zealand, USA, Canada, UK and Ireland ( p <0.025 for all), with peaks in the late winter/early spring months and troughs in the late summer/early autumn months. The top 11 rising topics were calcipotriol/betamethasone dipropionate, ustekinumab, apremilast, shampoo, eczema, guttate psoriasis, seborrhoeic dermatitis, dermatitis, psoriatic arthritis, atopic dermatitis and arthritis. Conclusion: There was a significant seasonal pattern for psoriasis, with peaks in the late winter/early spring and troughs in the late summer/early autumn. Further studies are warranted to confirm the seasonal pattern of psoriasis using clinical data and to explore the underlying mechanisms.